Satysfakcja zawodowa w ocenie jakości polityki rynku pracy w wybranych krajach Unii Europejskiej : podejście klasyfikacyjne - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula; Dziechciarz, Józef (Job Satisfaction as an Assessment Criterion of Labour Market Policy Efficiency : Classification Approach, 2005)
Authors proposed a new approach towards the efficiency assessment of the labour market policy. The proposal includes the main actors of the labour market - employee and their perception of the job related satisfaction as the measure of the policy quality. The data on job related satisfaction contained in the ECHP database (European Community Household Panel) where some 150 thousands respondents from 15 old EU member states are included was used. TwoStep Cluster Analysis was used for respondents' classification and multivariate statistical analysis framework was used for cross national comparisons and in order to identify Best European Practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 575-582